Root canal obturation by hybrid technique of thermomechanical gutta-percha compaction - Ilić Dragan (Serbian Medical Society - Dental Section, Belgrade, 2004)
The purpose of the study was to present and discuss the thermomechanical hybrid technique in root canal obturation and investigate the efficiency of apical hermeticity. The hybrid obturation technique is well explained and performed through the lexan models and extracted teeth in aim of better visualisation and comprehension as suggested by the author Tagger and McSpadden's articles. The technique consisted of lateral condensation of gutta-percha that was followed by thermomechanical compaction of the same mass using Ni-Ti flexible compactor. Firstly the master gutta-percha cone had to be adapted and then the master machine compactor selected for setting inside the canal. Upon laterally arranging gutta-percha cones, the master compactor was inserted between canal wall and gutta-percha. The master compactor was rotated for 5-6 seconds to creat heat to soften the cones to merge themselves and fill the first half of the canal. The bigger compactor served to fill the rest of the canal adding more gutta-percha cones. In comparison to the single cone and simple manual compaction techniques the hybrid technique is less time consuming more efficient in homogenicity and apical leakage. Considering the many device-consuming techniques the hybrid one is simpler to perform and cheaper as well. Precaution is to be taken when treating curved and narrow canals where much patience is needed due to possible compactor breakage and root fracture. It can be concluded that this hybrid technique is preferable particularly in cases of relatively straight canals with preserved apical foramen when time is to be saved for the radiographic and prosthetics procedure that has to be done during the same visit, which is very often convenient for patient and therapist.